Peran Kepolisian dalam Penerapan Diversi Konsep Restorative Justice Terhadap Anak Pelaku Tindak Pidana Penganiayaan di Kabupaten Berau Kalimantan Timur - Purba, Tommi Kardo; Setiyono, Setiyono (Postgraduate University of Merdeka Malang, 2024)
Children are subjects of criminal offenses as stated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which refers to children involved in criminal acts. Legal protection measures for children involved in criminal offenses come in various forms. One such form of legal protection is through a restorative justice approach. Based on the case study analyzed in this research, the author formulates the following issues: what is the concept of implementing restorative justice in Indonesia, what is the role of law enforcement, particularly the police, in the application of restorative justice, and what are the obstacles to implementing restorative justice at the Sambaliung Police Station, Berau Regency, East Kalimantan? The results of this study indicate that the goal of restorative justice is to restore damaged relationships, support the rehabilitation of offenders, and provide opportunities for victims to express their wishes and seek restitution. The obstacles faced by the Sambaliung Police Station in Berau Regency, East Kalimantan, are influenced by several factors, including the level of awareness of juvenile offenders, who may not fully understand the impact of their actions, fear or shame, particularly among juvenile offenders, to openly discuss their actions with victims, and the disagreement of victims' families regarding resolutions through restorative justice.